Origins of Proslavery Christianity White and Black Evangelicals in Colonial and Antebellum Virginia. - Irons, Charles F. (Chapel Hill : University of North Carolina Press, 2008)
In the colonial and antebellum South, black and white evangelicals frequently prayed, sang, and worshipped together. Even though white evangelicals claimed spiritual fellowship with those of African descent, they nonetheless emerged as the most effective defenders of race-based slavery. As Charles Irons persuasively argues, white evangelicals' ideas about slavery grew directly out of their interactions with black evangelicals. Set in Virginia, the largest slaveholding state and the hearth of the southern evangelical movement, this book draws from church records, denominational newspapers, slave.
Contents; Acknowledgments; Introduction. The Chief Cornerstone; One: Fishers of Men, 16801792; Two: Growing Pains, 17921815; Three: The Flourishing of Biracial Christianity, 18151831; Four: The Spiritual Challenge of Nat Turner, 18311835; Five: The Sectional Church, 18351856; Six: Reluctant, Evangelical Confederates, 18561861; Epilogue. Exodus, 18611870; Appendix A. Evangelical Virginians in 1790 and 1850; Appendix B. Distribution of Virginia Evangelicals in 1860; Appendix C. Church Governance; Notes; Bibliography; Index.
Description based on print version record.
Keywords: Turner, Nat, -- 1800?-1831 -- Influence; Slavery and the church -- Virginia -- History; Slavery and the church -- Southern States -- History; Slaves -- Religious life -- Virginia; African Americans -- Virginia -- Religion; Slaves -- Religious life -- Southern States; African Americans -- Southern States -- Religion; Evangelicalism -- Political aspects -- Southern States -- History; RELIGION / Christian Theology / Ethics; Electronic books